Evaluation of the Memory Enhancing Activity of Dichloromethane Fraction of the Methanolic Extract of Pycnanthus angolensis Stem Bark on Experimental Models of Memory Impairment - Ekwutosi Patricia, Chinwuba; Adewale Ganiyu, Bakare; Benneth, Ben-Azu; Ezekiel Olugbenga, Iwalewa (Drug Research, 2019)
Pycnanthus angolensis (Welw) Warb., Myristicaceae, is used extensively in ethnomedicine. Numerous health benefits have been ascribed to the use of different parts of P. angolensis including its role in cognitive function and inflammatory conditions. Hence, this study was undertaken to investigate the effect of stem bark of the plant on memory function in mice.The plant material was pulverized into powder and extracted by maceration with 80% methanol at room temperature for 48 h. This was subsequently fractionated using N-hexane, Dichloromethane (DCM) and Ethyl acetate. The Dichloromethane fraction which is the most potent fraction (25, 50 and 100 mg/kg) was evaluated for memory enhancing activity using the Y-maze (YMT), morris water maze (MWM) and the elevated plus maze (EPM) on D-galactose plus scopolamine and ketamine induced amnesia. The antioxidant markers and acetylcholinesterase (AChE) inhibiting effect of DCM were also investigated.The results obtained from the behavioural study indicates that the DCM fraction significantly (p<0.05) increased alternation behaviour of mice in the YMT, decreased the escape latency in the MWM paradigm and decreased the transfer latency in the EPM. Biochemically, DCM increased glutathione, and superoxide dismutase, but decreased malondialdehyde and AChE activity in the brain.The findings therefore suggests that the DCM possesses significant memory enhancing activity, which may be due to enhancement of antioxidant activity and cholinergic transmission. The attenuation of the effect of ketamine by the DCM may possibly result from an increase in NMDA receptor mediated neurotransmission and attenuation of oxidative stress.
Keywords: Memory function; Amnesia; Alzheimer’s disease; Oxidative stress